1988
DOI: 10.1177/030006058801600304
|View full text |Cite
|
Sign up to set email alerts
|

An Observer-Blind Crossover Study to Compare the Efficacies of Flurbiprofen, Indomethacin and Naproxen Given Orally and Rectally in the Relief of Night Pain and Morning Stiffness Due to Rheumatoid Arthritis

Abstract: An observer-blind three-period crossover study of flurbiprofen, indomethacin and naproxen was carried out in 56 patients with rheumatoid arthritis. The drugs were scheduled as two oral doses early in the day with a rectal suppository at night. The aims were to compare efficacy, principally as relief of night pain and morning stiffness, and safety. Flurbiprofen was clearly the most beneficial drug. Advantages over the comparators were demonstrated in terms of shorter duration of morning stiffness, reduced sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Placebo controlled studies have demonstrated that NSAIDs increase sleep quality [46, 47]. However, polysomnographic results have indicated that the administration of NSAIDs does not change the sleep architecture, sleep latency or sleep efficiency in patients with RA [48].…”
Section: Discussionmentioning
confidence: 99%
“…Placebo controlled studies have demonstrated that NSAIDs increase sleep quality [46, 47]. However, polysomnographic results have indicated that the administration of NSAIDs does not change the sleep architecture, sleep latency or sleep efficiency in patients with RA [48].…”
Section: Discussionmentioning
confidence: 99%
“…A manual review of complete reports eliminated 51 of them for the following reasons: administration path (7), review papers (4), pharmacokinetics studies (10) animal studies (9), indication (15), combined therapies (6), leading to the inclusion of the data of 14 studies (8,10,11,14,15,18,19,21,22,26–29). Four of them included naproxen as comparator (10,11,15,18), seven indomethacin (11,19,22,26–29), three aspirin (14,29), one ibuprofen (25) and one ketoprofen (8), accounting for a total of 1103 patient‐year. Four studies were multicentric (8,10,18,25).…”
Section: Resultsmentioning
confidence: 99%
“…Flurbiprofen is a non‐steroidal anti‐inflammatory agent of the phenylalkanoic acid series (ibuprofen, naproxen and ketoprofen) and has been shown in a number of pharmacological studies to be a potent and effective drug in the treatment of inflammatory conditions, notably, including rheumatoid diseases (8–29). Even then, flurbiprofen has been, since its marketing, mostly restricted to the ophthalmic, maxillofacial and gynaecological surgery spheres.…”
Section: Introductionmentioning
confidence: 99%